Comparison of Economic Efficiency of Rapeseed Production in Farms with Varied Fertilization Variants (Agricultural Engineering, 2016)
Intensive breeding is related to formation of considerable amount of manure which may be used as a natural fertilizer. Manure fertilization may cause reduction of the amount of applied mineral fertilizers and thus reduction of production costs. It may particularly relate to the species with great fertilization requirements such as winter rapeseed. The objective of the research was to compare economic efficiency of rapeseed production in two farms which use different fertilization variants. In one, only mineral fertilizers were used and in the second one – mineral fertilization was supplemented with manure organic fertilization. The use of manure caused reduction of expenditures on materials and raw materials used in production, in particular of fertilizers. At comparable yields obtained by two farms, technology based on manure fertilization proved to be more efficient.